HUBUNGAN KONDISI LINGKUNGAN DALAM RUMAH DENGAN KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS PATI I KABUPATEN PATI - Dinda Rachma Anggiani; Suhartono Suhartono; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Pneumonia is one of the biggest killers of children worldwide who is one of five deaths among children, with an estimated 1.8 million deaths annually. In 2015, the incidence of pneumonia in children under five years old in Pati regency of 191 cases. Puskesmas Pati I always ranked first incidence of pneumonia in Pati Regency, in 2015 children under five years old with pneumonia coverage handled Puskesmas Pati I still reached 58.8%, so it is less than the national target (100%). This study aims to determine the relationship of environmental conditions in the home with the incidence of pneumonia in children under five years old in Puskesmas I Pati Pati regency. This research uses observational analytic study with case control study design. The population of 5878 souls with a toddler age of the samples obtained 40 respondents case group and the control group of 40 respondents. Analyzed using univariate and bivariate with Chi Square test, and multivariate analysis with logistic regression test.The results show from 9 independent variables studied, there are 3 variables associated with the incidence of pneumonia in children under five years old, namely the presence of smokers in the home (p-value = 0.042; OR = 3.400; 95% CI = 1.156 to 9.996), use of mosquito coils (p Value-= 0.000; OR = 9.000; 95% CI = 2.698 to 30.021), and the type of house floor (p-value = 0.009; OR = 4.265; 95% CI = 1.531 to 11.886). It can be concluded that the condition of the home environment associated with pneumonia in children under five years old in Puskesmas I Pati Pati Regency is the presence of a smoker in the house, use of mosquito coils, and the type of house floor.